Decoupled power control for a modular-multilevel-converter-based hybrid AC–DC grid integrated with hybrid energy storage - Zhang, Lei (2020)
This paper presents a decoupled power control strategy for a modular multilevel converter (MMC)-based hybrid ac-dc grid integrated with a hybrid energy storage system. This system can mitigate the active power fluctuations caused by intermittent renewable generation and also realize reactive power compensation as required by voltage regulation. The proposed hybrid ac-dc system has a novel configuration in which batteries and supercapacitors are distributed into the upper arm and the lower arm of the MMC, respectively. Therefore, it is possible to design fully decoupled power control and simultaneously optimize the performances of batteries and supercapacitors. First, the system modeling and operational principles of the MMC are briefly introduced in this paper. On the basis of these analyses, the power decoupling between the upper arm and the lower arm is presented to realize different control objectives. Moreover, battery state-of-charge balancing control and supercapacitor voltage control are also presented, which are crucial for ensuring the normal operation of these energy storage components and the proposed MMC-based hybrid ac-dc grid. Finally, the proposed system and its control strategies are verified by laboratory experimental results.